On the nomenclature of fossil Potamogeton (Potamogetonaceae) - Doweld, Alexander B. (Phytotaxa, 2016)
12 fossil species names of Potamogeton described from the Miocene to Pleistocene sediments of Eurasia based on fruit endocarp findings were found to be later homonyms of some extant and fossil species of Potamogeton and are here replaced by new names: Potamogeton baluevae (replacement name for fossil P. decipiens), P. borsukiae (replacement name for fossil P. carinatus), P. gorbunovii (replacement name for fossil P. pseudofriesii), P. jakubovskajae (replacement name for fossil P. praenatans), P. kasakorum (replacement name for fossil P. pliocenicus), P. kolesnikovae (replacement name for fossil P. stylatus), P. kondinskajae (replacement name for fossil P. obtusus), P. novorossicus (replacement name for fossil P. corniculatus), P. pashkovii (replacement name for fossil P. striatus), P. rutiloides (replacement name for fossil P. palaeorutilus), P. snigirevskajae (replacement name for fossil P. microcarpus), P. volgensis (replacement name for fossil P. tataricus). Nomenclature and typification of names are given along with their palaeogeographic and stratigraphic data.